2011
DOI: 10.1111/j.1600-0838.2009.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of physical activity with muscular fitness in adolescents

Abstract: The aim of this study was to examine the associations between objectively assessed physical activity (PA) and muscular fitness (MF) in adolescents, and to determine whether only resistance training exercise is associated with the increase of MF. A sample of 211 Spanish adolescents (105 girls) wore the ActiGraph monitor for 7 days. Participants also completed a fitness evaluation including three MF tests (handgrip strength, a 60‐s abdominal test and a standing broad jump), a cardiorespiratory fitness assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 40 publications
6
29
0
Order By: Relevance
“…The results verified in the present study are in agreement with the findings in the research carried out with the participation of 789 North American adolescents aged 12-19 years, in which active commuting to school was inversely associated to BMI score; however, no association was observed with WC 10 . In another study involving 6,797 adolescents aged 9-11 from 12 countries, it was observed those who actively commuted to school had lower BMI values and lower odds of developing abdominal obesity 5 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results verified in the present study are in agreement with the findings in the research carried out with the participation of 789 North American adolescents aged 12-19 years, in which active commuting to school was inversely associated to BMI score; however, no association was observed with WC 10 . In another study involving 6,797 adolescents aged 9-11 from 12 countries, it was observed those who actively commuted to school had lower BMI values and lower odds of developing abdominal obesity 5 .…”
Section: Discussionsupporting
confidence: 82%
“…In addition, exploring the different contexts within the school environment can bring significant contributions to the planning of actions and interventions, as adolescents spend much of their time in school, and Physical Education classes and school recess may be privileged spaces to promote the practice of physical activities 9 . Another important context for adolescents is how much physical activity they perform to improve muscle strength / endurance, since adequate levels of these components are predictors of adequate health 10 . In addition, investigating global physical activity is justified, since failure to comply with physical activity recommendations is considered an independent factor for increased abdominal fat and excess body weight 11 .…”
Section: Introductionmentioning
confidence: 99%
“…18 The adolescents who were involved in resistance training had significantly higher muscular strength scores than youth in low and medium tertiles of physical activity, but no significant differences were found when they were compared with nonlifters from the highest tertile of physical activity. 19 The results of the present study and the previous studies together suggest that duration of vigorous physical activity is an important predictor of, and may be strongly associated with, age-related, site-specific loss of thigh muscle.…”
Section: Discussionsupporting
confidence: 55%
“…Our Wndings suggest that low muscular Wtness levels aVect clustered CVD risk already in youth, and the underlying mechanism through which this occurs is at least partially independent of those associated with CRF. The literature posits potential mechanisms related to muscle Wbre type or composition (Harrison and Leinwand 2008), or participation in vigorous physical activity (Martinez-Gomez et al 2011). Limitations evident in this study include: cross-sectional design, predominance of individuals of Caucasian-European ethnicity, the lack of gold-standard muscular Wtness and CRF laboratory-based measures that were not able to be implemented in a Weldwork setting.…”
Section: Discussionmentioning
confidence: 98%